YouTube as a second classroom: Self-regulate language learning of Sociology students in Blitar - Fu'ad Sholikhi (Indonesian Journal of English Language Studies (IJELS), 2026)
Technology is evolving at a rapid pace, affecting lecturers and students across the world in their efforts to harness educational journeys, particularly in English learning. YouTube is a free application that serves as an excellent program for Sociology students at the Islamic University of Balitar (Unisba) to grasp cultural elements in English.  This qualitative study, conducted using a narrative technique, exposed the deeper experience of six sociology students who used this program for self-regulated learning in an ESP class. The findings were evaluated using assessment, revolution, and coda. The findings reveal that the students utilize YouTube regularly, they choose the proper information relevant to their major, they get feedback from the instructor, and they use it to supplement traditional ESP classes. The findings also show that the source category is the most prominent, as the students believe it helps them find a wide range of cultural elements on the internet. The findings show that social and cultural categories fail to be incorporated into the independent learning process, as students place greater emphasis on academic achievement rather than conducting research into specific cultural and linguistic contexts.